The Effect of Service Quality and Corporate Image on Customer Loyalty through Customer Satisfaction as an Intervening Variable at PT. Bank Kalteng - Setiawan, Andre (International Journal on Social Science, Economics and Art, 2024)
The number of banks in Indonesia has increased competition in the banking sector. Customer loyalty is a sign that a bank has won the competition. Customer loyalty is influenced by service quality, company image and customer satisfaction. The problem of leakage and sale of customer data is a phenomenon of this study, besides that there are still gaps in the results of previous research on the variables used in this study, making researchers interested in conducting research again using these variables. The method used in this research was a quantitative method with primary data. The data collection technique in this research involved distributing questionnaires to customers of PT. Bank Kalteng via Google Forms. The data analysis tool used in this study was Structural Equation Modeling (SEM) using SmartPLS version 4.1.0. The results of this study indicate that service quality and corporate image have a positive and significant effect on customer satisfaction. Service quality, corporate image, and customer satisfaction have a positive and significant effect on customer loyalty. Service quality and corporate image indirectly affect customer loyalty positively through customer satisfaction as an intervening variable.